Ways and Opportunities to Increase the Integration Cooperation of Higher Education and Professional Educational Institutions - Kurbanova Khumora Begmurodovna; Djurayeva Nasiba Rustamovna (European Science Publishing, 2024)
In the development of an integrative partner of higher education and professional educational institutions, recommendations on Professional education, training of qualified specialists suitable for the labor market, specifics of professonal education, organization and management of educational processes in professional educational institutions are widely covered.
Keywords: Professional education, educational process in Professional educational institutions, cooperation of higher education and professional educational institutions, Organization of educational process, integrative cooperation, management of educational process.